Principle of evidence of John Amos Comenius as a basis for the development of pedagogical research techniques and instruments - Maksimović, Jelena; Sretić, Sanja (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
The methodology of pedagogy belongs to the youngest group of pedagogical disci-plines. The first thoughts about the basic postulates of the methodology of pedagogy were rec-ognized long ago, even in the pedagogical paradigm of John Amos Comenius (1592-1670), who created support for the methodology of pedagogy as an integral component of pedagogical science. After the presentation of the basic concepts of the pedagogical theory of this Moravian thinker, the principle of evidence in his pedagogical theory is considered in this paper. A review was made of the influence Comenius left on his followers Jean-Jacques Rousseau (1712-1778) and Johann Heinrich Pestalozzi (1746-1827), especially from the point of view of further devel-opment of the principles of evidence in their education theories. In this paper, we have con-firmed our hypothesis about the compatibility of the principle of evidence with research tech-niques and instruments. Proactively action by Comenius represents a turning point not only in the field of pedagogy development as a science and its disciplines, but also in the field of human development in general. Regarding that, there is a need for a new pedagogical discipline, Comeniology, which will give a new perspective to this pedagogical doctrine and will foster a critical review in relation to his pedagogical theory. According with our research subject, we have presented some of our dilemmas and questions to which the Comeniology as a new scien-tific discipline could give an answer, and therefore a kind of scientific contribution. Based on the previous methodological achievements, Comeniology remains committed to discovering the origins of other research techniques and methods in the pedagogical postulates of Comenius, to determine the applicability of the Comenius pedagogical principles with regard to the changes and challenges facing the contemporary teaching process, to open the issue of pedagogical psy-chological competencies of teachers for the application of the golden rule of Comenius and its other principles, to continue engagement of Comenius in the qualitative educational function of a modern school, but also to consider the influence of other factors (family environment) that may influence the choice of teaching principles and methods.